The Dual-Role of Methylglyoxal in Tumor Progression – Novel Therapeutic Approaches - Leone, Alessia; Nigro, Cecilia; Nicolò, Antonella; Prevenzano, Immacolata; Formisano, Pietro; Beguinot, Francesco; Miele, Claudia (Frontiers in Oncology, 2021)
One of the hallmarks of cancer cells is their metabolic reprogramming, which includes the preference for the use of anaerobic glycolysis to produce energy, even in presence of normal oxygen levels. This phenomenon, known as “Warburg effect”, leads to the increased production of reactive intermediates. Among these Methylglyoxal (MGO), a reactive dicarbonyl known as the major precursor of the advanced glycated end products (AGEs), is attracting great attention. It has been well established that endogenous MGO levels are increased in several types of cancer, however the MGO contribution in tumor progression is still debated. Although an anti-cancer role was initially attributed to MGO due to its cytotoxicity, emerging evidence has highlighted its pro-tumorigenic role in several types of cancer. These apparently conflicting results are explained by the hormetic potential of MGO, in which lower doses of MGO are able to establish an adaptive response in cancer cells while higher doses cause cellular apoptosis. Therefore, the extent of MGO accumulation and the tumor context are crucial to establish MGO contribution to cancer progression. Several therapeutic approaches have been proposed and are currently under investigation to inhibit the pro-tumorigenic action of MGO. In this review, we provide an overview of the early and latest evidence regarding the role of MGO in cancer, in order to define its contribution in tumor progression, and the therapeutic strategies aimed to counteract the tumor growth.